PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - indarsari, marliana saputri; winedar, mustika (Prodi Akuntansi FEB UNITOMO, 2020)
This study intends to carry out an analysis related to the effect of the variable tax planning and variable tax burden on earnings management. As for the targets for this research are food and beverage sub-sector manufacturing companies that have been listed on the Stock Exchange in 2016 to 2018. While the data and materials needed in this study are obtained from the annual financial statements obtained from the website www.idx.co.id. Then the sampling method used in this study is to use a purposive sampling method and 9 company samples have been obtained. While the researchers used three methods of data analysis namely the classic assumption test, multiple linear regression test and hypothesis testing. The results shown in the study are that the tax planning variable has no effect on earnings management partially, but the deferred tax burden has an effect on partial earnings management. While simultaneously, the variable tax planning and deferred tax expense variables together have an influence on earnings management.